Protestant Fundamentalism as a Threat to Latin American Democracy: The Case of Brazil - Tapia-Cahuana, Gherson (2025)
Protestant fundamentalism in Brazil has grown in relevance, aligning itself with the political far right and af-fecting significant events such as the 2016 coup and Lula's arrest in 2018. The main objective is to analyze how Protestant fundamentalism undermines democratic values and fuels authoritarianism in the country. The methodology employed is qualitative, utilizing documentary analysis and a literature review. The research reveals that Protestant fundamentalism is not only a religious phenomenon but also a potential threat to de-mocracy and human rights, exacerbating social polarization and justifying authoritarian attitudes. It is suggested that democratic institutions be strengthened, interreligious dialogue and civic education promoted, and the authoritarian discourse of fundamentalist groups be dismantled to protect the rights and integrity of the dem-ocratic state.